Uncovering diverse reactivity of NHCs withdiazoalkane: C-H activation, C=C bond formation,and access to N-heterocyclic methylenehydrazine - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Science, 2024)
N-heterocyclic carbenes (NHCs) have attracted significant attention due to their strong sigma-donating capabilities, as well as their transition-metal-like reactivity towards small molecules. However, their interaction with diazoalkanes remains understudied. In this manuscript, we explore the reactivity of a series of stable carbenes, encompassing a wide range of electronic properties, with Me3SiCHN2. 5-SIPr activates the C-H bond of Me3SiCHN2, resulting in the formation of a novel diazo derivative (1), while carbenes such as 5-IPr, 6-SIPr, and diamido carbene yield N-heterocyclic methylenehydrazine derivatives (3, 4, and 8). The reaction of Me3SiCHN2 with 5-ItBu unexpectedly leads to the formation of a triazole ring linked with the imidazole moiety via a CC double bond (6) alongside the azine product (7). Substituting the diazoalkane with diazoester consistently yields azine derivatives (9-12 and 14). Only in the case of 5-ItBu, an imidazolium salt with tetrazenide anion (13) was obtained as a side product. The reaction of 4 with HCl resulted in the desilylprotonation to form a salt, 5a, which undergoes deprotonation upon using bases such as Et3N and KHMDS to form N-heterocyclic methylene hydrazine, 5. Theoretical calculations have been conducted to elucidate the diverse mechanisms underlying product formation.